Dialectical Versus Linear Thinking Shapes People’s Anticipation of Climate Change - Li, Liman Man Wai; Mei, Dongmei; Li, Wen-Qiao; Ito, Kenichi (Frontiers in Psychology, 2021)
Dialectical thinking refers to a constellation of beliefs that consist of expectation of change, tolerance of contradiction, and holism. The current research explored whether dialectical thinking would affect people’s anticipation of climate change, which has been propagated globally. Study 1 compared the responses between Chinese participants, representing people from cultures that promote dialectical thinking, and North American participants, representing people from cultures that promote linear thinking. The results showed that Chinese participants demonstrated a stronger non-linear pattern regarding the anticipation of climate change as compared with American participants, in which Chinese participants were more likely to anticipate a stable trend but less likely to anticipate an increasing trend for global warming. Study 2 with a manipulation of dialectical and linear thinking was conducted and provided some generally supportive evidence for the causal relation between dialectical beliefs and anticipation of climate change. Implications for cross-cultural environmental research and international climate change education programs were discussed.